Identification of loci associated with schizophrenia by genome-wide association and follow-up - O'Donovan, M; Craddock, N; Norton, N; Williams, H; Peirce, T; Moskvina, V; Nikolov, I; Hamshere, M; Carroll, L; Georgieva, L; Dwyer, S; Holmans, P; et al. (2008)
We carried out a genome-wide association study of schizophrenia (479 cases, 2,937 controls) and tested loci with P < 10-5 in up to 16,726 additional subjects. Of 12 loci followed up, 3 had strong independent support (P < 5 × 10-4), and the overall pattern of replication was unlikely to occur by chance (P = 9 × 10-8). Meta-analysis provided strongest evidence for association around ZNF804A (P = 1.61 × 10-7) and this strengthened when the affected phenotype included bipolar disorder (P = 9.96 × 10-9). © 2008 Nature Publishing Group.